One year experience in the treatment of familial hypercholesterolaemia with simvastatin. Issue 801 (July 1992) - Quiney, J.; Watts, G. F.; Kerr-Muir, M.; Slavin, B.; Lewis, B.
Abstract : Patients with heterozygous familial hypercholesterolaemia (FH) have a substantially increased risk of atherosclerosis due to very high plasma levels of cholesterol. Recent evidence has shown that coronary heart disease in these patients may regress with lipid-lowering therapy. In this study the efficacy and safety of simvastatin, an inhibitor of the enzyme 3-hydroxy-3-methylglutaryl coenzyme A, was investigated in 30 patients with FH over a period of one year. Substantial reductions in the plasma concentrations of total cholesterol (-28%), low-density lipoprotein (LDL) cholesterol (-32%), intermediate-density lipoprotein (IDL) cholesterol and apolipoprotein (apo) B (-33%) were achieved with 20 mg/day of simvastatin; there were no significant changes in triglycerides high-density lipoprotein cholesterol or apo A. In contrast to previous studies, 40 mg/day of simvastatin did not result in a further statistically significant fall in LDL cholesterol, IDL cholesterol or apo B in the group as a whole. The drug was well tolerated and no adverse clinical or laboratory events were recorded. In particular, no ophthalmological, hepatic or renal disorders were observed and there were no sleep disturbances. We conclude that simvastatin is an efficacious and safe drug to treat patients with heterozygous FH and that rarely will the dose need to be increased above 20 mg/day.